Positive Attitude of Pregnant Women to Use Herbal Treatments in order to Prevent the Transmission of Covid-19 - Nila Qurniasih; Hikmah Ifayanti; Inggit Primadevi; Nova Elok Mardliyana (Health Notions, 2022)
Indonesia had been confirmed case of Covid-19, and the case increasing until 66.578 in Oktober 2020. In Lampung Province, the Covid-19 also seen increase up to 62,8%. The Covid-19 infection is at risk of being transmitted to pregnant woment it is feared that it will have a dangerous impact on the mother and fetus as miscarriage and preterm labor. Herbal’s treatment to the prevention infection of Covid-19, it are considered low risk to teratogenic effect compared pharmacological intervention. This research study purpose is to investigated of characteristic responden within positive attitude in prevention transmission Covid-19 at pregnant woman to use herbal treatment. This research study was quantitatif with descriptive analytic design. The subject in this study were 43 pregnant women, selected using accidental sampling. The data were collected using questionnaire in January 2021. The most of the respondents had positive attitude towards the use of herbal medicine in preventing Covid-19. Keywords: Covid-19; prevention; transmission; herbal treatment; attitude; pregnant women